Vanadium and cadmium in vivo effects in cardiac muscle: metal accumulation and oxidative stress markers - S. Soares, Sandra (2008)
Several biological studies associate vanadium and cadmium with the production of reactive oxygen species (ROS), leading to lipid peroxidation and antioxidant enzymes alterations. The present study aims to analyse and compare the oxidative stress responses induced by an acute intravenous exposure (1 and 7 days) to a sub-lethal concentration (5 mM) of two vanadium solutions, containing different vanadate noligomers (n=1–5 or n=10), and a cadmium solution on the cardiac muscle of the marine teleost Halobatrachus didactylus (Lusitanian toadfish). It was observed that vanadium is mainly accumulated in mitochondria (1.33±0.26 μM), primarily when this element was administrated as decameric vanadate, than when administrated as metavanadate (432±294 nM), while the highest content of cadmium was found in cytosol (365±231 nM). Indeed, decavanadate solution promotes stronger increases in mitochondrial antioxidant enzymes activities (catalase: +120%; superoxide dismutase: +140%) than metavanadate solution. On contrary, cadmium increases cytosolic catalase (+111%) and glutathione peroxidases (+50%) activities. It is also observed that vanadate oligomers induce in vitro prooxidant effects in toadfish heart, with stronger effects induced by metavanadate solution. In summary, vanadate and cadmium are differently accumulated in blood and cardiac subcellular fractions and induced different responses in enzymatic antioxidant defence mechanisms. In the present study, it is described for the first time the effects of equal doses of two different metals intravenously injected in the same fish species and upon the same exposure period allowing to understand the mechanisms of vanadate and cadmium toxicity in fish cardiac muscle.